Biorthogonal Expansion of Non-Symmetric Jack Functions - Sahi, S.; Zhang, G. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We find a biorthogonal expansion of the Cayley transform of the non-symmetric Jack functions in terms of the non-symmetric Jack polynomials, the coefficients being Meixner-Pollaczek type polynomials. This is done by computing the Cherednik-Opdam transform of the non-symmetric Jack polynomials multiplied by the exponential function.